Understanding temperature and magnetic-field actuated magnetization polarity reversal in the Prussian blue analogue Cu0.73Mn0.77[Fe(CN)6].zH2O, using XMCD. (24th February 2016) - Lahiri, Debdutta; Choi, Yongseong; Yusuf, S M; Kumar, Amit; Ramanan, Nitya; Chattopadhyay, Soma; Haskel, Daniel; Sharma, Surinder M
Abstract: We have investigated the microscopic origin of temperature and magnetic-field actuated magnetization reversal in Cu0 .73 Mn0.77 [Fe(CN)6 ]. z H2 O, using XMCD. Our results show a fair deviation from the mean-field-theory in the form of different ordering temperatures of Fe and Mn sublattices. A preferential sign reversal of Mn spin under magnetic field and different spin cant angles for the two sublattices have also been observed. An antiferromagnetic coupling between the Fe and Mn sublattices along with different ordering temperatures (sublattice decoupling) for these sublattices explain the temperature-dependent magnetization reversal. Whereas, Mn spin reversal alone (under external magnetic field) is responsible for the observed field-dependent magnetization reversal. The dissimilar magnetic behavior of Fe and Mn sublattices in this cubic 3d-orbital system has been understood by invoking disparity and competition among inter-sublattice magnetic control parameters, viz. magnetic Zeeman energy, exchange coupling constant and magnetic anisotropy constant. Our results have significant design implications for future magnetic switches, by optimizing the competition among these magnetic control parameters.